Relapse of imported Plasmodium vivax malaria is related to primaquine dose: a retrospective study - Townell Nicola; Looke David; McDougall David; McCarthy James S (Malaria Journal, 2012)
Abstract Background Relapsing Plasmodium vivax infection results in significant morbidity for the individual and is a key factor in transmission. Primaquine remains the only licensed drug for prevention of relapse. To minimize relapse rates, treatment guidelines have recently been revised to recommend an increased primaquine dose, aiming to achieve a cumulative dose of ≥6 mg/kg, i.e. ≥420 mg in a 70 kg patient. The aims of this study were to characterize the epidemiology of P . vivax infection imported into Queensland Australia, to determine the rates of relapse, to investigate the use of primaquine therapy, and its efficacy in the prevention of relapse. Methods A retrospective study was undertaken of laboratory confirmed P. vivax infection presenting to the two major tertiary hospitals in Queensland, Australia between January 1999 and January 2011. Primaquine dosing was classified as no dose, low dose (<420 mg), high dose (≥420 mg), or unknown. The dose of primaquine prescribed to patients who subsequently relapsed that prescribed to patients who did not relapse. Results Twenty relapses occurred following 151 primary episodes of P . vivax infection (13.2%). Relapses were confirmed among 3/21 (14.2%), 9/50 (18.0%), 1/54 (1.9%) and 7/18 (38.9%) of patients administered no dose, low dose, high dose and unknown primaquine dose respectively. High dose primaquine therapy was associated with a significantly lower rate of relapse compared to patients who were prescribed low dose therapy (OR 11.6, 95% CI 1.5-519, p = 0.005). Conclusions Relapse of P. vivax infection is more likely in patients who received low dose primaquine therapy. This study supports the recommendations that high dose primaquine therapy is necessary to minimize relapse of P. vivax malaria.